The use of technology in cancer prehabilitation: a systematic review - Tay, San San; Zhang, Fuquan; Neo, Edmund Jin Rui (Frontiers in Oncology, 2024)
Aim: This review aimed to evaluate the effectiveness and feasibility of cancer prehabilitation programs delivered through technological enablers compared to conventional face-to-face interventions. Methods: A systematic review was conducted, searching PubMed, Embase, and CINAHL for studies published from inception to February 6, 2024. Studies were included if they involved adult cancer patients in primary research, utilized technology for prehabilitation, and assessed functional, psychological, and quality of life outcomes. Results: Sixteen studies were included, encompassing wearables, apps, teleprehabilitation, and virtual reality. All studies reported feasibility, but challenges included technical issues, lack of supervision, and non-compliance. Effectiveness depended on intervention rigor and technology type. Wearables offered objective monitoring but faced compliance issues. Videoconferencing provided supervision and could mitigate compliance concerns. Multimodal programs and intervention-specific outcome measures were recommended. Conclusion: Technology-based prehabilitation programs seem feasible, but effectiveness depends on intervention design and technology employed. Future research should focus on developing robust evidence to guide clinical practice and explore the potential of integrated technological solutions.